PENGARUH FINANCIAL DISTRESS, UKURAN PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCREN - Sholihati, Muthiatus; Satyawan, Made Dudy (STIE Perbankan Indonesia, 2024)
The purpose of this study was to determine the effect of financial distress, company size and good corporate governance on going concern audit opinion. The population of this study is the non-cyclical consumer sector, more precisely the food and beverage subsector because the sector weakened when the co-19 pandemic occurred so that there is a possibility of changes regarding companies that are given an audit opinion by the auditor regarding business continuity. The number of companies sampled was 45 companies based on certain criteria. Based on the purposive sampling method, the number of samples in this study was 135 samples. This study uses logistic regression analysis as a hypothesis test. The results showed that financial distress has a positive effect on going concern audit opinion, while company size and good corporate governance have a negative effect on going concern audit opinion. Keywords: Financial Distress, Company Size, Good Corporate Governance and Going concern Audit Opinion